1995
DOI: 10.1007/bf02444660
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraosseous receptors in afferent and motor reaction modulation

Abstract: Acute experiments on cats demonstrated facilitation effects of afferent reactions, and segmentary motor reactions during stimulation of sciatic nerves and inhibition of corticofugal motor reactions induced by electrical stimulation of ilium osteoreceptors. Key Words: nociception; intraosseous receptors; radicular syndromeThe osteoreceptor system remains one of the least studied parts of sensory system physiology. This might be due to the fact that so far no holistic concept has yet emerged regarding its role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that both electrical stimulation and increase in pressure within bone marrow generate a blood pressure increase that may be indicative of nociceptive activation. 22 An increase in intraosseous pressure has been shown to activate fine-diameter afferent nerve fibers arising from bone marrow, as do irritant and inflammatory agents such as H + and K + ions and histamine and bradykinin. 23 These findings suggest that intraosseous nociceptors are activated by various kinds of stimuli including an increase in intraosseous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both electrical stimulation and increase in pressure within bone marrow generate a blood pressure increase that may be indicative of nociceptive activation. 22 An increase in intraosseous pressure has been shown to activate fine-diameter afferent nerve fibers arising from bone marrow, as do irritant and inflammatory agents such as H + and K + ions and histamine and bradykinin. 23 These findings suggest that intraosseous nociceptors are activated by various kinds of stimuli including an increase in intraosseous pressure.…”
Section: Discussionmentioning
confidence: 99%